Infrared Light Induced Bending of Liquid Crystalline Elastomer Composite-Silicone Bilayer Films - (:unkn) unknown (My University, 2013)
This research centers on infrared (IR) light-induced bending of liquid crystalline elastomers (LCE) composite-silicone bilayer films. Two new developments are presented in this thesis. First, the reversible infrared (IR) induced bending of 0.1% (w/w) single walled nanotube (SWNT)-LCE/silicone bilayer films were successfully prepared and used for fabrication of functioning devices such as folding, grabbing, and crawling structures. Second, the use of adding a filler (absorbs specific wavelength range), such as Dye 1002, into the LCE matrix achieved wavelength selectivity in LCE systems. The 0.2% (wt/wt) Dye 1002-LCE/silicone bilayer films demonstrated bending under a 980 nm laser source but no bending under a 1342 nm laser source. These developments are evidence that LCE systems can be used for making a variety of IR light-induced functional devices and that LCE systems can be tuned to absorb a specific wavelength range of IR light by adding a filler such as Dye 1002 into the LCE network.